Report: Geneva Visit: 4-9 July 1999 - Laetitia J King; Valerie J Ehlers (AOSIS, 2000)
This report provides a brief introduction to Geneva and its many international organisations and aims to share some of the insights gained during discussions held with various key persons at the World Health Organisation (WHO), the International Committee of the Red Cross, and the International Nursing Review (INR), the official journal of the International Nursing Council. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.